Increased mortality associated with weekend hospital admission: a case for expanded seven day services?. (5th September 2015) - Freemantle, Nick; Ray, Daniel; McNulty, David; Rosser, David; Bennett, Simon; Keogh, Bruce E; Pagano, Domenico
Abstract : Nick Freemantle and colleagues discuss the findings of their updated analysis of weekend admissions and the implications for service design